Portable Small Items Stair-Lift (Detachable) - Sayed Azman, Syed Faiq Irfan (Universiti Teknologi PETRONAS, 2021)
Based on the statistics, falls or Stair Falls specifically proved to pose a big hazard or threat to people as its injuries range from just minor bruising to a severe hip fracture which has a terrifying 1-year mortality rate of about 25%. On top of that, even surviving such an accident would take away a big chunk of independence and quality of life from the victim. That apart, the main thing which is focused in this work are falls which are caused by loss of balance. This loss of balance when further branched is due to having an additional load on oneself which interferes with their natural center of gravity. To help eliminate the hardships faced by those groups of people with disabilities or lack of balance while going up the stairs, the Portable Small Items StairLift was created. The device prototype will have the ability to carry small items up and downstairs through the stair handrails.